Corrigendum to “Trifluoroacetic acid and ocular malformations in rabbits: Proposed mechanisms of action” [Reprod. Toxicol. 143 (2026) 109258] - Julian French; Jason Manton; Maaike E. Schutte; Stephanie Melching-Kollmuss; Steffen Schneider; Ivana Fegert; Anja Hueser; Birgit Neumann; Michael Temerowski; Lisa Bertomeu; Richard Bartlett (Reproductive Toxicology, 2026)

Trifluoroacetic acid and ocular malformations in rabbits: Proposed mechanisms of action - Julian French; Jason Manton; Maaike E. Schutte; Stephanie Melching-Kollmuss; Steffen Schneider; Ivana Fegert; Anja Hueser; Birgit Neumann; Michael Temerowski; Lisa Bertomeu; Richard Bartlett (Reproductive Toxicology, 2026)

Impact of root observation windows on plant performance, root development, and rhizosphere-microbial communities during late vegetative growth of field-grown winter wheat - Loreen Sommermann; Jan Helge Behr; Narges Moradtalab; Saskia Windisch; Soumitra Paul Chowdhury; Michael Rothballer; Ingo Schellenberg; Doreen Babin; Kornelia Smalla; Lorrie Maccario; SØren J. SØrensen; Uwe Ludewig; et al. (Plant and Soil, 2026)
Background and Aims Root observation windows (RW) installed in the field provide a tool for non-destructive monitoring of root development and rhizosphere processes. However, the highly invasive installation process, which requires cutting soil profiles, may affect plant development and, ultimately, the outcome of the experiments. This study systematically compares plant development with and without the installation of RW. Methods Using the location of a long-term field experiment, the responses of winter wheat to different intensities of tillage, N-fertilization, and use of fungicides were compared for plants grown along root windows and in undisturbed control plots. Sampling was performed during late vegetative growth, six weeks after RW installation, with comparisons of shoot and root biomass, root length, mineral nutritional status, stress-related gene expression, stress metabolites, and the composition of microbial communities reflecting rhizosphere (RH) conditions. Results The presence of RW did not significantly affect most of the parameters analyzed. As an exception, RW plants showed increased foliar concentrations of several nutrients (K, Mg, Ca, Cu, Mn), potentially attributable to reduced inter-plant competition because RW were installed along border rows of the experimental plots. By contrast, N-fertilization intensity and fungicide use affected plant biomass, root growth, and fungal communities. Tillage intensity primarily affected fine-root production, the composition of RH-microbial communities, and physiological stress indicators in leaf tissue. Conclusion The results suggest only a limited influence on performance of winter wheat six weeks after RW installation under the selected experimental conditions, with plant responses and experimental results comparable to undisturbed controls.

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Bundesweite Entwicklung der Grundwasserstände seit 1991: Langzeittrends, Variabilität und Auswirkungen der jüngsten Trockenphase - Maria Wetzel; Stefan Broda; Mariana Gomez; Markus Zaepke; Patrick Clos; Stefan Kunz; Tanja Liesch; Marc Ohmer; Bastian Habbel; Michel Wingering; Bernhard Pitschka; Antje Roucka; et al. (Grundwasser, 2026)
Zusammenfassung Die Studie untersucht die Entwicklung der Grundwasserstände in Deutschland anhand von 5844 Messstellen sowie deren Reaktionsdynamik gegenüber klimatologischen Antrieben im Referenzzeitraum 1991–2020. Zusätzlich wird die Entwicklung seit 2018 im Kontext der außergewöhnlichen Dürreperiode betrachtet, um die Reaktionsfähigkeit und Vulnerabilität der Grundwassersysteme gegenüber extremen klimatischen Bedingungen zu bewerten. Erstmals erfolgt diese Auswertung bundesweit einheitlich und in enger Zusammenarbeit mit den zuständigen Landesbehörden. An 43 % der untersuchten Messstellen werden signifikante Trends festgestellt, überwiegend in Form fallender Grundwasserstände mit einem Medianrückgang von 0,9 cm pro Jahr. Dies entspricht einem jährlichen Rückgang von 0,5 %, bezogen auf die Spannweite der jeweiligen Grundwasserganglinie. Diese Entwicklungen sind deutschlandweit erkennbar, jedoch regional unterschiedlich ausgeprägt und überwiegend klimatisch bedingt. Um Unterschiede in der Reaktionsdynamik systematisch zu erfassen, werden die Messstellen anhand ihrer Autokorrelationslängen in vier Dynamikklassen eingeteilt. Mit abnehmender Dynamik zeigt sich für den Referenzzeitraum eine Zunahme langfristiger Trends (von −0,3 % pro Jahr in Dynamikklasse 1 bis −1,16 % pro Jahr in Klasse 4) sowie eine höhere Persistenz klimatischer Effekte. Träge Systeme reagieren verzögert und sind damit nachhaltiger von Niedrigständen betroffen (Median: 9,8 Monate), während schnell reagierende Systeme kürzere Niedrigstandsphasen (Median: 2,2 Monate) aufweisen und sich rascher erholen. Besonders in der Entwicklung seit 2018 werden diese Unterschiede deutlich: Rund 60 % der trägen Messstellen weisen über fünf Jahre hinweg anhaltend niedrige Grundwasserstände auf, wobei etwa 20 % neue Niedrigstände erreichen und damit unterhalb der Minimalwerte der Referenzperiode liegen. Die Ergebnisse verdeutlichen den engen Zusammenhang zwischen klimatischer Variabilität und Grundwasserdynamik und bilden eine Grundlage für die fortlaufende Bewertung der Grundwasserstandsentwicklung in Deutschland.

Think pink 2.0 - Description of Roseobacter cerffii sp. nov., isolated from the chromerid alga Vitrella brassicaformis, and reclassification of Sulfitobacter sabulilitoris as Billmartinia sabulilitoris, gen. nov., comb. nov. - Jörn Petersen; Victoria Ringel; Orsola Päuker; Anja Frühling; Manfred Rohde; Michael Jarek; Cathrin Spröer; Boyke Bunk; Katharina Huber-Fischer; Silke Pradella; Heike M. Freese; Julia Koblitz; et al. (Systematic and Applied Microbiology, 2026)

Empathy in Adults with Acquired Brain Injury: a Systematic Review and Meta-Analysis - Emily Clements; Kristin Naragon-Gainey; Michael Weinborn; Carmela Pestell; Dawn Neumann; David Preece; Rodrigo Becerra (Neuropsychology Review, 2026)
Empathy is the ability to recognise, share and understand others’ emotional states. Increasing evidence suggests that empathy may be impacted by acquired brain injury (ABI), with consequences for social and emotional functioning. However, the literature has been characterised by inconsistent findings and small sample sizes. To address these limitations, we provide the first meta-analytic review of empathy in adults with ABI. Specifically, the review aimed to quantify the degree of impairment in adults with ABI across four empathy-related domains: cognitive, affective, empathic concern (e.g. sympathy) and personal distress. We also sought to estimate the prevalence of deficits in each area and explore whether demographic and injury factors moderate impairment. A systematic search yielded 29 studies measuring self-reported empathy in adults with ABI versus healthy, matched peers. A series of random-effects meta-analyses revealed moderate deficits in cognitive empathy (Hedges’ g = − 0.68, 95% CI [− 0.87, − 0.50]) and affective empathy (Hedges’ g = − 0.43, 95% CI [− 0.65, − 0.21]), as well as small-to-moderate deficits in empathic concern (Hedges’ g = − 0.38, 95% CI [− 0.63, − 0.13]). No significant difference was found for personal distress. We estimated the proportion of ABI participants scoring equal to or more than 1 SD below the normative mean to be 15.3–35.0%, depending on the empathy subcomponent. Our results highlight that empathy deficits may play an important role in functional or emotional difficulties post-brain injury. This demonstrates the need for routine clinical assessment of empathy in survivors of brain injury and the need to develop interventions which target both cognitive and affective components.

Association between cardiovascular-kidney-metabolic syndrome and risks of 14 age-related health outcomes in primary prevention older population - Zhen Zhou; Kevan R. Polkinghorne; Andrew M. Tonkin; Robyn L. Woods; Anping Cai; Sophia Zoungas; Michelle A. Fravel; Michael E. Ernst; Chao Zhu; Mark Nelson; Johannes T. Neumann; Kerry M. Sheets; et al. (GeroScience, 2026)

On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

From molecular to immuno-pharmacology: Schmiedeberg Medal for Klaus Resch - Michael U. Martin; Detlef Neumann; Michael Kracht (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Succession of Bacteria and Archaea Within the Soil Micro‐Food Web Shifts Soil Respiration Dynamics - Mandip Tamang; Johannes Sikorski; Miriam van Bommel; Marc Piecha; Tim Urich; Liliane Ruess; Katharina Huber; Meina Neumann‐Schaal; Michael Pester (Environmental Microbiology, 2024)
Bacterivorous nematodes are important grazers in the soil micro‐food web. Their trophic regulation shapes the composition and ecosystem services of the soil microbiome, but the underlying population dynamics of bacteria and archaea are poorly understood. We followed soil respiration and 221 dominant bacterial and archaeal 16S rRNA gene amplicon sequencing variants (ASVs) in response to top‐down control by a common bacterivorous soil nematode, Acrobeloides buetschlii , bottom‐up control by maize litter amendment and their combination over 32 days. Maize litter amendment significantly increased soil respiration, while A. buetschlii addition caused an earlier peak in soil respiration. Underlying bacterial and archaeal population dynamics separated into five major response types, differentiating in their temporal abundance maxima and minima. In‐depth analysis of these population dynamics identified a broad imprint of A. buetschlii grazing on dominant bacterial ( Acidobacteriota, Bacteroidota, Gemmatimonadota, Pseudomonadota ) and archaeal ( Nitrososphaerota ) ASVs. Combined bottom‐up control by maize litter and top‐down control by A. buetschlii grazing caused a succession of soil microbiota, driven by population changes first in the Bacteroidota , then in the Pseudomonadota and finally in the Acidobacteriota and Nitrososphaerota . Our results are an essential step forward in understanding trophic modulation of soil microbiota and its feedback on soil respiration.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Letter to the editor regarding Collard et al. (2023): “Persistence and mobility (defined as organic-carbon partitioning) do not correlate to the detection of substances found in surface and groundwater: Criticism of the regulatory concept of persistent and mobile substances” - Hans Peter H. Arp; Raoul Wolf; Sarah E. Hale; Sivani Baskaran; Juliane Glüge; Martin Scheringer; Xenia Trier; Ian T. Cousins; Harrie Timmer; Roberta Hofman-Caris; Anna Lennquist; André D. Bannink; et al. (Science of The Total Environment, 2024)

Climate change and stock returns in the european market: An environmental intensity approach - Maria-Glòria Barberà-Mariné; Laura Fabregat-Aibar; Andreu-Michael Neumann-Calafell; Antonio Terceño (Journal of Environmental Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Paleoenvironmental, paleoclimatic, and organic matter assessment of the hybrid Kharita Formation (Albian) in the Abu Gharadig Basin, Egypt: Integration between palynology, organic petrography, and organic geochemistry - Ahmed Mansour; Thomas Gentzis; Sameh S. Tahoun; Mohamed S. Ahmed; Michael Wagreich; Humberto Carvajal-Ortiz; Jacob Neumann; Ahmed E. Radwan (Marine and Petroleum Geology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Rhodococcus pseudokoreensis sp. nov. isolated from the rhizosphere of young M26 apple rootstocks - Peter Kämpfer; Stefanie P. Glaeser; Jochen Blom; Jacqueline Wolf; Sarah Benning; Michael Schloter; Meina Neumann-Schaal (Archives of Microbiology, 2022)
The Gram-positive strain R79 T , isolated from the rhizosphere of young M26 apple rootstocks, was investigated by a polyphasic taxonomic approach. Phylogenetic identification based on the full-length 16S rRNA gene sequence revealed highest 16S rRNA gene sequence similarity to the type strains of Rhodococcus wratislaviensis (99.6%) and Rhodococcus opacus (99.2%) followed by Rhodococcus imtechensis (98.9%). All other 16S rRNA gene sequence similarities were below 98.65%. A phylogenomic tree calculated based on a whole-genome sequence also showed a distinct clustering with the type strain of Rhodococcus koreensis. Average nucleotide identity (ANI) values between whole-genome sequences of R79 T and the closest related type strains were below 95% supported the novel species status. The DNA G + C content of R79 T was 67.24% mol. Predominant fatty acids were C 16:0, C 15:0 and C 17:1ω8c . The strain contained MK8-H 2 as the major respiratory quinone. The polar lipid profile consists of diphosphatidylglycerol and phosphatidylethanolamine, as well as of some unidentified lipids. The peptidoglycan type of the strain is A1γ meso -diaminopimelic acid. Based on the obtained genotypic and phenotypic, including chemotaxonomic data, we conclude that R79 T represents a novel species of the genus Rhodococcus , for which the name Rhodococcus pseudokoreensis sp. nov. is proposed. The type strain is R79 T (= DSM 113102 T = LMG 32444 T = CCM 9183 T ).

Complex and flexible catabolism in Aromatoleum aromaticum pCyN1 - Patrick Becker; Annemieke Döhmann; Lars Wöhlbrand; Daniela Thies; Christina Hinrichs; Ramona Buschen; Daniel Wünsch; Meina Neumann‐Schaal; Dietmar Schomburg; Michael Winklhofer; Richard Reinhardt; Ralf Rabus (Environmental Microbiology, 2022)
Summary Large quantities of organic matter are continuously deposited, and (a)biotic gradients intersect in the soil–rhizosphere, where biodegradation contributes to the global cycles of elements. The betaproteobacterial genus Aromatoleum comprises cosmopolitan, facultative denitrifying degradation specialists. Aromatoleum aromaticum . pCyN1 stands out for anaerobically decomposing plant‐derived monoterpenes in addition to monoaromatic hydrocarbons, polar aromatics and aliphatics. The catabolic network's structure and flexibility in A . aromaticum pCyN1 were studied across 34 growth conditions by superimposing proteome profiles onto the manually annotated 4.37 Mbp genome. Strain pCyN1 employs three fundamentally different enzymes for C–H‐bond cleavage at the methyl groups of p ‐cymene/4‐ethyltoluene, toluene and p ‐cresol respectively. Regulation of degradation modules displayed substrate specificities ranging from narrow (toluene and cyclohexane carboxylate) via medium‐wide (one module shared by p ‐cymene, 4‐ethyltoluene, α‐phellandrene, α‐terpinene, γ‐terpinene and limonene) to broad (central benzoyl‐CoA pathway serving 16 aromatic substrates). Remarkably, three variants of ATP‐dependent (class I) benzoyl‐CoA reductase and four different β‐oxidation routes establish a degradation hub that accommodates the substrate diversity. The respiratory system displayed several conspicuous profiles, e.g. the presence of nitrous oxide reductase under oxic and of low‐affinity oxidase under anoxic conditions. Overall, nutritional versatility in conjunction with network regulation endow A . aromaticum pCyN1 with broad adaptability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New phylogenetic insights into the African catfish families Mochokidae and Austroglanididae - Frederic D. B. Schedel; Albert Chakona; Brian L. Sidlauskas; Michael O. Popoola; Nadine Usimesa Wingi; Dirk Neumann; Emmanuel J. W. M. N. Vreven; Ulrich K. Schliewen (Journal of Fish Biology, 2022)
Several hundred catfish species (order: Siluriformes) belonging to 11 families inhabit Africa, of which at least six families are endemic to the continent. Although four of those families are well‐known to belong to the ‘Big‐Africa clade’, no previous study has addressed the phylogenetic placement of the endemic African catfish family Austroglanididae in a comprehensive framework with molecular data. Furthermore, interrelationships within the ‘Big‐Africa clade’, including the most diverse family Mochokidae, remain unclear. This study was therefore designed to help reconstruct inter‐ and intrarelationships of all currently valid mochokid genera, to infer their position within the ‘Big Africa clade’ and to establish a first molecular phylogenetic hypothesis of the relationships of the enigmatic Austroglanididae within the Siluriformes. We assembled a comprehensive mitogenomic dataset comprising all protein coding genes and representing almost all recognized catfish families ( N = 33 of 39) with carefully selected species ( N = 239). We recovered the monophyly of the previously identified multifamily clades ‘Big Asia’ and ‘Big Africa’ and determined Austroglanididae to be closely related to Pangasiidae, Ictaluroidea and Ariidae. Mochokidae was recovered as the sister group to a clade encompassing Auchenoglanididae, Claroteidae, Malapteruridae and the African Schilbeidae, albeit with low statistical support. The two mochokid subfamilies Mochokinae and Chiloglanidinae as well as the chiloglanid tribe Atopochilini were recovered as reciprocally monophyletic. The genus Acanthocleithron forms the sister group of all remaining Mochokinae, although with low support. The genus Atopodontus is the sister group of all remaining Atopochilini. In contrast to morphological reconstructions, the monophyly of the genus Chiloglanis was strongly supported in our analysis, with Chiloglanis macropterus nested within a Chiloglanis sublineage encompassing only other taxa from the Congo drainage. This is an important result because the phylogenetic relationships of C. macropterus have been controversial in the past, and because we and other researchers assumed that this species would be resolved as sister to most or all other members of Chiloglanis . The apparent paraphyly of Synodontis with respect to Microsynodontis provided an additional surprise, with Synodontis punu turning out to be the sister group of the latter genus.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Macrofauna as a major driver of bentho‐pelagic exchange in the southern North Sea - Andreas Neumann; Justus E. E. van Beusekom; Annika Eisele; Kay‐Christian Emeis; Jana Friedrich; Ingrid Kröncke; Ella Lu Logemann; Julia Meyer; Céline Naderipour; Ulrike Schückel; Alexa Wrede; Michael L. Zettler (Limnology and Oceanography, 2021)
The contribution of sediments to nutrient cycling of the coastal North Sea is strongly controlled by the intensity of fluxes across the sediment water interface. Pore‐water advection is one major exchange mechanism that is well described by models, as it is determined by physical parameters. In contrast, biotransport (i.e., bioirrigation, bioturbation) as the other major transport mechanism is much more complex. Observational data reflecting biotransport, from the German Bight for example, is scarce. We sampled the major sediment provinces of the German Bight repeatedly over the years from 2013 to 2019. By employing ex situ whole core incubations, we established the seasonal and spatial variability of macrofauna‐sustained benthic fluxes of oxygen and nutrients. A multivariate, partial least squares analysis identified faunal activity, in specifically bioturbation and bioirrigation, alongside temperature, as the most important drivers of oxygen and nutrient fluxes. Their combined effect explained 63% of the observed variability in oxygen fluxes, and 36–48% of variability in nutrient fluxes. Additional 10% of the observed variability of fluxes were explained by sediment type and the availability of plankton biomass. Based on our extrapolation by sediment provinces, we conclude that pore‐water advection and macrofaunal activity contributed equally to the total benthic oxygen uptake in the German Bight.

A temperature binning approach for multi-sector climate impact analysis - Marcus C. Sarofim; Jeremy Martinich; James E. Neumann; Jacqueline Willwerth; Zoe Kerrich; Michael Kolian; Charles Fant; Corinne Hartin (Climatic Change, 2021)
Characterizing the future risks of climate change is a key goal of climate impacts analysis. Temperature binning provides a framework for analyzing sector-specific impacts by degree of warming as an alternative or complement to traditional scenario-based approaches in order to improve communication of results, comparability between studies, and flexibility to facilitate scenario analysis. In this study, we estimate damages for nine climate impact sectors within the contiguous United States (US) using downscaled climate projections from six global climate models, at integer degrees of US national warming. Each sector is analyzed based on socioeconomic conditions for both the beginning and the end of the century. The potential for adaptive measures to decrease damages is also demonstrated for select sectors; differences in damages across adaptation response scenarios within some sectors can be as much as an order of magnitude. Estimated national damages from these sectors based on a reactive adaptation assumption and 2010 socioeconomic conditions range from $600 million annually per degree of national warming for winter recreation to $8 billion annually per degree of national warming for labor impacts. Results are also estimated per degree of global temperature change and for 2090 socioeconomic conditions.

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Journal Club - Marisa Schübel; Klaus Hantke; Javier Garcia Varo; Andreas Seiffert-Störiko; Stefanie Schulz; Petra Neumann-Staubitz; Theresa Gewering; Daniela Kruck; Sylvia Schnell; Michael Steinert (BIOspektrum, 2020)

Cellular organization and histogenesis of adenosquamous carcinoma of the pancreas: evidence supporting the squamous metaplasia concept - Werner Boecker; Katharina Tiemann; Joerg Boecker; Marieta Toma; Michael H. Muders; Thomas Löning; Igor Buchwalow; Karl J. Oldhafer; Ulf Neumann; Bernd Feyerabend; Andre Fehr; Göran Stenman (Histochemistry and Cell Biology, 2020)
Adenosquamous carcinoma of the pancreas (ASCAP) is characterized by conventional pancreatic ductal adenocarcinoma (PDAC) and squamous carcinoma components with at least 30% of the tumour showing squamous differentiation. To get further insight into the histogenesis of these lesions, we analysed the cellular organization of ASCAP compared to PDACs. Using Immunohistochemistry and triple immunofluorescence labelling studies for keratins, p63, p40, MUC1, MUC2, MUC5AC, Ki67, and EGFR we demonstrate that many ASCAPs contain a transitional zone between the K8/18-positive adenocarcinomatous component and the p63+ /p40+ /K5/K14+ squamous component initiated by the expression of p63 in K8/18+ adenocarcinomatous cells and the appearance of basally located p63+ K5/14+ cells. p63+ K5/14+ cells give rise to fully developed squamous differentiation. Notably, 25% of conventional PDACs without histologically recognizable squamous component contain foci of p63+ p40+ and K5/14+ cells similar to the transitional zone. Our data provide evidence that the squamous carcinoma components of ASCAPs originate from pre-existing PDAC via transdifferentiation of keratin K8/18-positive glandular cells to p63-, p40-, and keratin K5/14-positive squamous carcinoma cells supporting the squamous metaplasia hypothesis. Thus our findings provide new evidence about the cellular process behind squamous differentiation in ASCAPs.

Quantification of PpIX-fluorescence of cerebral metastases: a pilot study - Johannes Knipps; Igor Fischer; Lisa M. Neumann; Marion Rapp; Maxine Dibué-Adjei; Christiane Freiin von Saß; Jan-Malte Placke; Hendrik-Jan Mijderwijk; Hans-Jakob Steiger; Michael Sabel; Jan-Frederick Cornelius; Marcel A. Kamp (Clinical & Experimental Metastasis, 2019)

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Überwachung der vertikalen Stabilität der Stauanlage Schräh im Wägital - Marita Scheller; Michael Möser; Gunnar Lelle-Neumann (WASSERWIRTSCHAFT, 2018)

Indicator-Based Soil Moisture Monitoring of Wetlands by Utilizing Sentinel and Landsat Remote Sensing Data - Randolf Klinke; Helga Kuechly; Annett Frick; Michael Förster; Tobias Schmidt; Ann-Kathrin Holtgrave; Birgit Kleinschmit; Daniel Spengler; Carsten Neumann (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2018)

All-printed planar photoelectrochemical cells with digitated cathodes for the oxidation of diluted aqueous pollutants - Petr Dzik; Michal Veselý; Martina Pachovská; Michael Neumann-Spallart (Environmental Science and Pollution Research, 2017)

Native plasmids restrict growth of Phaeobacter inhibens DSM 17395: Energetic costs of plasmids assessed by quantitative physiological analyses - Kathleen Trautwein; Sabine Eva Will; Reiner Hulsch; Uwe Maschmann; Katharina Wiegmann; Michael Hensler; Victoria Michael; Hanna Ruppersberg; Daniel Wünsch; Christoph Feenders; Meina Neumann‐Schaal; Sabine Kaltenhäuser; et al. (Environmental Microbiology, 2016)
Summary Plasmid carriage is associated with energetic costs, and thus only those plasmids providing fitness benefits are stably maintained in the host lineage. Marine bacteria of the Roseobacter clade harbor up to 11 extrachromosomal replicons, adding lifestyle‐relevant and possibly habitat success‐promoting functions to their genomic repertoire. Phaeobacter inhibens DSM 17395 is a nutritionally versatile representative, carrying three stable and functionally distinct plasmids (65, 78, and 262 kb). The present study investigates the physiological and energetic consequences of plasmid carriage in P. inhibens DSM 17395, employing mutants cured from all native plasmids in every possible combination (seven different). Cultivation in process‐controlled bioreactors with casamino acids as organic substrate revealed a complex physiological response, suggesting existence of functional interconnections between the replicons. Deletion of the 262 kb plasmid boosted growth rate (>3‐fold) and growth efficiency (yields for carbon, O 2 and CO 2 ), which was not observed for the 65 or 78 kb plasmid. Carriage of the 262 kb plasmid was most costly for the wild type, i.e. contributing ∼50% to its energetic (dissimilatory) expenditures. Cost–benefit analysis of plasmid carriage reflects the high value of plasmids for niche specialization of P. inhibens DSM 17395 and most likely also for related Phaeobacter species.

Unterwasserabgabe nicht aus dem Grundablass — Motive und Folgen alternativer Ausleittiefen - Martin Schultze; Marieke Frassl; Michael Weber; Bertram Boehrer; Karsten Rinke; Ralf Sudbrack; Vincenz Neumann; Hartmut Willmitzer; Markus Möller; Wilfried Scharf (WASSERWIRTSCHAFT, 2016)

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

The effect of skin fatty acids on Staphylococcus aureus - Yvonne Neumann; Knut Ohlsen; Stefanie Donat; Susanne Engelmann; Harald Kusch; Dirk Albrecht; Michael Cartron; Alexander Hurd; Simon J. Foster (Archives of Microbiology, 2015)

Forest floor vegetation response to nitrogen deposition in Europe - Thomas Dirnböck; Ulf Grandin; Markus Bernhardt‐Römermann; Burkhardt Beudert; Roberto Canullo; Martin Forsius; Maria‐Theresia Grabner; Maria Holmberg; Sirpa Kleemola; Lars Lundin; Michael Mirtl; Markus Neumann; et al. (Global Change Biology, 2014)
Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1,335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load ( CL ) for eutrophication effects ( P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover ( P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species ( P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCL emp N). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.

Import and export of biological samples from tropical countries–considerations and guidelines for research teams - Swen C. Renner; Dirk Neumann; Michael Burkart; Ute Feit; Peter Giere; Andreas Gröger; Axel Paulsch; Cornelia Paulsch; Mario Sterz; Katrin Vohland (Organisms Diversity & Evolution, 2012)

Information content of female copulation calls in wild long-tailed macaques (Macaca fascicularis) - Antje Engelhardt; Julia Fischer; Christof Neumann; Jan-Boje Pfeifer; Michael Heistermann (Behavioral Ecology and Sociobiology, 2012)

The alternative Pharaoh approach: stingless bees mummify beetle parasites alive - Mark K. Greco; Dorothee Hoffmann; Anne Dollin; Michael Duncan; Robert Spooner-Hart; Peter Neumann (The Science of Nature, 2010)

Spatial modelling for the development of agri-environmental programs - Barbara Neumann; Michael Lütz; Beatrice Schüpbach; Erich Szerencsits (Regional Environmental Change, 2009)

The Role of Corneocytes in Skin Transport Revised—A Combined Computational and Experimental Approach - Steffi Hansen; Arne Naegel; Michael Heisig; Gabriel Wittum; Dirk Neumann; Karl-Heinz Kostka; Peter Meiers; Claus-Michael Lehr; Ulrich F. Schaefer (Pharmaceutical Research, 2009)

Rare royal families in honeybees, Apis melliferas - Robin F. A. Moritz; H. Michael; G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Rare royal families in honeybees, Apis mellifera - Robin F. A. Moritz; H. Michael G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

The SeKT Joint Research Project: Definition of reference conditions, control sediments and toxicity thresholds for limnic sediment contact tests (2 pp) - Ute Feiler; Wolfgang Ahlf; Sebastian Höss; Henner Hollert; Helga Neumann-Hensel; Michael Meller; Jürgen Weber; Peter Heininger (Environmental Science and Pollution Research, 2005)

Isolation and characterization of Dehalospirillum multivorans gen. nov., sp. nov., a tetrachloroethene-utilizing, strictly anaerobic bacterium - Heidrun Scholz-Muramatsu; Anke Neumann; Michael Memer; Edward Moore; Gabriele Diekert (Archives of Microbiology, 1995)

Isolation and characterization of Dehalospirillum multivorans gen. nov., sp. nov., a tetrachloroethene-utilizing, strictly anaerobic bacterium - Heidrun Scholz-Muramatsu; Anke Neumann; Michael Memer; Edward Moore; G. Diekert (Archives of Microbiology, 1995)

Contribution of olfactory navigation and non-olfactory pilotage to pigeon homing - Hans G. Wallraff; Michael F. Neumann (Behavioral Ecology and Sociobiology, 1989)